Partners in Caribbean development : NGOs and donors meet in Grenada, 6-9 November 2001 (2002)
Reports on the meeting held to enable NGO leaders from the region to meet with selected donors. Notes that the meeting explored ways of improving collaboration, as genuine partners in Caribbean development, with a view to contributing towards the sustainability of the region.
Keywords: DEVELOPMENT AID